2012
DOI: 10.1038/onc.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive proteasomal degradation of TWIST-1 in epithelial–ovarian cancer stem cells impacts differentiation and metastatic potential

Abstract: Epithelial-mesenchymal transition (EMT) is a critical process for embryogenesis but is abnormally activated during cancer metastasis and recurrence. This process enables epithelial cancer cells to acquire mobility and traits associated with stemness. It is unknown whether epithelial stem cells or epithelial cancer stem cells are able to undergo EMT, and what molecular mechanism regulates this process in these specific cell types. We found that Epithelial Ovarian Cancer Stem cells (EOC stem cells) are the sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 61 publications
(88 reference statements)
4
81
0
1
Order By: Relevance
“…18 We have shown recently that ovarian cancer cells expressing CD44 are highly tumorigenic, have capabilities of self-renewal, and recapitulate the heterogeneous phenotype of the tumor. 8,10,38 In addition, CD44þ cells are resistant to chemotherapy and are able to survive treatment with conventional drugs such as carboplatin and paclitaxel. 39 The findings described in this study are in support of the hypothesis that the CSCs are significant players in chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…18 We have shown recently that ovarian cancer cells expressing CD44 are highly tumorigenic, have capabilities of self-renewal, and recapitulate the heterogeneous phenotype of the tumor. 8,10,38 In addition, CD44þ cells are resistant to chemotherapy and are able to survive treatment with conventional drugs such as carboplatin and paclitaxel. 39 The findings described in this study are in support of the hypothesis that the CSCs are significant players in chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…These patient samples were obtained from patients at Yale New Haven Hospital (New Haven, CT) who were diagnosed with stage III/IV serous ovarian cancer and propagated as described previously (9,10,14,(28)(29)(30)(31)(32)(33) …”
Section: Methodsmentioning
confidence: 99%
“…More importantly, it allows us to test the efficacy of treatment against the mesenchymal cancer subtype. We previously showed that spheroid formation is a function of OCSCs and that this correlates with the acquisition of a mesenchymal phenotype, augmented migratory capacity, and enhanced chemoresistance (32). Thus, we tested the ability of TRX-E-002-1 to induce cell death in 3D spheroid cultures of OCSC2 by monitoring spheroid integrity using kinetic imaging.…”
Section: Activity Of Trx-e-002-1 Against Heterogeneous Ovarian Cancermentioning
confidence: 99%
“…Our analysis implicated several miRNAs as dysregulated in ccRCC for the first time including upregulation of miR-494 reported to target PTEN, 40 142-3p implicated in angiogenesis 20 as discussed above, 22-3p involved in the regulation of differentiation of mesenchymal stem cells 41 and also known to be a repressor of PTEN 42 as well as other miRNAs such as miR-1225-5p and 342-3p of which little or nothing is known of targets and functional role. We also identified downregulation of the let-7 family involved in the inhibition of cell growth and proliferation, 17 miR-200a-3p and 429 which are both members of the miR-200 family that target the ZEB1 and ZEB2 transcriptional repressors of E-cadherin and so are implicated in EMT and tumor invasion, 17 199a-5p involved in the regulation of the IKKβ/ NFκB and PTEN/AKT pathways 43 and other miRNAs such as miR-30c-5p of unknown function. Analysis by DIANA mirpath on a set of the 20 most upregulated and 30 most downregulated miRNAs identified the PI3K-Akt, MAPK, Wnt, TGF-β, p53, mTOR, Hedgehog, and VEGF signaling pathways, various pathways of metabolism, EMT, apoptosis, pathways in cancer, renal cell carcinoma, and other cancers as over-represented (P < 0.05) (Sup.…”
Section: 15mentioning
confidence: 99%